Human Resource Management Activities, Employee Retention and Turnover in Nepalese Service Sector Organizations - Pradhan, Gopal Man; Shrestha, Prakash; Wagle, Debendra Kumar (Journal of Business Management and Information Systems, 2024)
This study aims to examine the impact of human resource management (HRM) activities, which include employee promotion, training and development, and financial rewards on employee retention and employee turnover trends. This survey comprised managerial and assistant-level employees from commercial banks and other service businesses. The results show an influential and positive relationship between employee promotion, training and development financial rewards, and employee retention. In contrast, there is a considerable negative association between employee promotion, training and development and financial rewards, and employee turnover in service sector organizations. The retention of employees in the organization for a long time would be supportive from two perspectives: firstly, it can develop the working efficiency of the employees and secondly, employees become loyal to the organization. This greatly contributes to the efficient and successful functioning of the organization in the society. However, high employee turnover would have a negative impact on the long-term functioning of the organizations.